Naturalness translation: A parameter of translation quality assessment in a pragmatic perspective - Wisudawanto, Rahmat (Journal of English Language Teaching and Learning (JETLE), 2024)
A parameter in assessing the translation quality is naturalness. The naturalness in translation adopted the concept of translation as an act of communication. It means that translation has a proper structure and choice of words according to a particular context. The article discusses the naturalness of translation based on pragmatic studies. The study used the utterances in the tourism text Solo Calendar of Event 2018 as data since the text had a communication function in conveying persuasive messages to tourists. In measuring the naturalness, the translation must achieve the equivalence in sentence structure and the types as well as the intended meaning of an utterance. The results indicated that the translation was categorized as fully equivalence with 70.49% of total data while the less equivalence and inequivalence of translation are 24.59% and 4.91% respectively from total data. The naturalness of translation from a pragmatic point of view requires understanding the objective of communication. It involves understanding utterance functions from the source text and achieving equivalence in translation. Translators also consider the choices of utterances since they can impact the target audience. The analysis of naturalness using pragmatic perspective offers new insight in the translation quality assessment.